1997
DOI: 10.1046/j.1365-3083.1997.d01-418.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Polyreactive IgM Monoclonal Antibodies with Blocking Activity Against Self‐Reactive IgG

Abstract: Natural IgM antibodies have been found to be involved in the control of IgG reactivity in normal serum. The authors investigated the blocking activity of four human IgM monoclonal antibodies (BY-2, BY-7, BY-10 and IRM-7) derived from B-cells from blood samples of three renal dialysis patients, which had shown multispecific properties similar to those observed for natural polyreactive autoantibodies. To achieve this, competitive inhibition assays were performed with these MoAbs on the binding of IgG purified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Similar inhibitions of the IgG autoAb activity have been reported in the serum of both mice [22,23] and humans [24], where polyclonal and monoclonal IgM were found to inhibit autologous and homologous serum IgG. These IgM-associated inhibitions of IgG were not due to a competition for the same Ag but probably to anti-Fab binding [22].…”
Section: Discussionsupporting
confidence: 73%
“…Similar inhibitions of the IgG autoAb activity have been reported in the serum of both mice [22,23] and humans [24], where polyclonal and monoclonal IgM were found to inhibit autologous and homologous serum IgG. These IgM-associated inhibitions of IgG were not due to a competition for the same Ag but probably to anti-Fab binding [22].…”
Section: Discussionsupporting
confidence: 73%
“…The inhibitory effect of IgM mAb is mediated by V-regiondependent interactions with the autoreactive IgG, as shown by the ability of these antibodies to block the binding of F(abЈ) 2 fragments of autoreactive IgG to their respective autoantigens (15). The blocking activity was found to be dose-dependent, with maximal inhibition occurring at a specific molar ratio between the patient's IgG and a given mAb, supporting the concept of a functional idiotypic network regulating autoimmune responses.…”
Section: Natural Autoantibodies As Protective Immunoglobulinsmentioning
confidence: 76%
“…In the context of autoimmunity, IgM autoantibodies have often been considered to be simply nonpathogenic, but they appear to be actually protective. 34,35 Mice deficient in serum IgM exhibit spontaneous autoimmunity (eg, the production of anti-DNA IgG), indicating the role of IgM in protecting against the development of autoimmunity. 36 Antigen microarray informatics study, however, has demonstrated that the IgM antibodies produced by neonatal humans recognize mostly self molecules that are associated with major autoimmune diseases later in life.…”
Section: Discussionmentioning
confidence: 99%